Construction and applications of a B vitamin genetic resource for investigation of vitamin‐dependent metabolism in maize. (3rd November 2019) - Suzuki, Masaharu; Wu, Shan; Mimura, Manaki; Alseekh, Saleh; Fernie, Alisdair R.; Hanson, Andrew D.; McCarty, Donald R.
Summary: The B vitamins provide essential co‐factors for central metabolism in all organisms. In plants, B vitamins have surprising emerging roles in development, stress tolerance and pathogen resistance. Hence, there is a paramount interest in understanding the regulation of vitamin biosynthesis as well as the consequences of vitamin deficiency in crop species. To facilitate genetic analysis of B vitamin biosynthesis and functions in maize, we have mined the UniformMu transposon resource to identify insertional mutations in vitamin pathway genes. A screen of 190 insertion lines for seed and seedling phenotypes identified mutations in biotin, pyridoxine and niacin biosynthetic pathways. Importantly, isolation of independent insertion alleles enabled genetic confirmation of genotype‐to‐phenotype associations. Because B vitamins are essential for survival, null mutations often have embryo lethal phenotypes that prevent elucidation of subtle, but physiologically important, metabolic consequences of sub‐optimal (functional) vitamin status. To circumvent this barrier, we demonstrate a strategy for refined genetic manipulation of vitamin status based on construction of heterozygotes that combine strong and hypomorphic mutant alleles. Dosage analysis of pdx2 alleles in endosperm revealed that endosperm supplies pyridoxine to the developing embryo. Similarly, a hypomorphic bio1 allele enabled analysis of transcriptome and metabolome responses to incipient biotin deficiency in seedling leaves. We show that systemic pipecolic acid accumulation is an early metabolic response to sub‐optimal biotin status highlighting an intriguing connection between biotin, lysine metabolism and systemic disease resistance signaling. Seed‐stocks carrying insertions for vitamin pathway genes are available for free, public distribution via the Maize Genetics Cooperation Stock Center. Significance Statement: The B vitamin genetic resource for maize provides a rich source of hypomorphic and loss‐of‐function mutations that are key to delineating B vitamin‐dependent metabolic, developmental, disease and stress response phenotypes. We demonstrate the use of hypomorphic alleles to probe developmental and metabolic consequences of sub‐lethal pyridoxine and biotin deficiency states.